Prenatal phenotype features and genetic etiology of the Williams-Beuren syndrome and literature review - Wang, Yunan; Liu, Chang; Hu, Rong; Geng, Juan; Lu, Jian; Zhao, Xianzhe; Xiong, Ying; Wu, Jing; Yin, Aihua (Frontiers in Pediatrics, 2023)
Objective: To share our experience on prenatal diagnosis of Williams-Beuren syndrome and to improve the understanding, diagnosis, and monitoring of this disease in fetuses. Methods: The study retrospectively evaluated fourteen fetal cases of Williams-Beuren syndrome diagnosed prenatally by single nucleotide polymorphism array (SNP-array). Clinical data were reviewed, including maternal characteristics, indications for prenatal diagnosis, sonographic features, SNP-array results, pregnancy outcomes and follow-ups. Results: A total of fourteen fetuses were diagnosed with WBS and their prenatal phenotypes were assessed retrospectively. In our study cohort, common ultrasound features were IUGR, congenital cardiovascular defects, abnormal fetal placental Doppler indices, thickened NT and polyhydramnios. Other less common ultrasound features include fetal hydrops, hydroderma, bilateral pleural effusion, subependymal cysts, etc. Parental chromosome analysis was performed in seven pairs of parents, and all the deletions on chromosome 7q11.23 were de novo. Conclusion: Prenatal ultrasound findings of WBS cases are highly variable, with IUGR, cardiovascular abnormalities and abnormal fetal placental Doppler indices, being the most common intrauterine phenotypes. Our cases expand the prenatal phenotypes of WBS, including cardiovascular abnormalities RAA combined with PRUV and elevated S/D. Further technical advances in the NIPT technology are likely to enhance prenatal diagnosis and therefore affect the epidemiology of WBS in the future. In the meantime, next-generation sequencing may become the most widely used strategy in prenatal diagnosis in the near future.